In Memoriam Julia Obertreis (1969–2023) - Сергій Посохов (Вісник Харківського національного університету імені В.Н. Каразіна. Історія)
This memorial text pays tribute to Julia Obertreis (1969–2023), who was a distinguished professor specializing in modern and contemporary Eastern European history at the Friedrich-Alexander University in Erlangen-Nuremberg (Friedrich-AlexanderUniversität Erlangen-Nürnberg). The author recounts the significant milestones in her career, her major research contributions, and her notable visits to the V. N. Karazin Kharkiv National University. Additionally, the text reflects on the various collaborative events and initiatives she was involved in.